Transforming the rice sector - Gyimah-Brempong, Kwabena; Johnson, Michael E.; Takeshima, Hiroyuki (University of Pennsylvania Press, 2016)
This book presents analyses of primary and secondary data on the production, domestic market, processing, consumption, and trade for the rice economy in Nigeria using a variety of economic models. The goal has been to identify constraints and opportunities for policy in order to transform and improve the domestic rice sector's competitiveness with imports. In this chapter, we summarize the key results and findings from this analysis and discuss the broad policy implications.